Action is demonstrative of critical reflection and “disorienting dilemma” is démodé - Carol A. Olszewski; Catherine A. Hansman (Adult Education Research Conference, 2021)
This paper explores transformative learning and 1) roles of decision-making and actions as outward expressions of critical reflection and 2) vocabulary that encapsulates the essence of the “disorienting dilemma.”
Keywords: Transformative learning; critical reflection; disorienting dilemma; pivotal experiences